Development of a Method to Detect Three Monohydroxylated Polycyclic Aromatic Hydrocarbons in Human Urine by Liquid Chromatographic Tandem Mass Spectrometry - Xiaotao Zhang; Hongwei Hou; Wei Xiong; Qingyuan Hu (Journal of Analytical Methods in Chemistry)
A liquid chromatographic tandem mass spectrometry method (LC-MS/MS) for the simultaneous determination of 1-hydroxypyrene (1-OHP), 3-hydroxybenzo[a]pyrene (3-OHBaP), and 3-hydroxybenz[a]anthracene (3-OHBaA) in human urine has been developed. With the exception of 3-OHBaP at a low spiking level, the average recoveries were greater than 80%. The method has good accuracy (72.1–107.7%) and reproducibility (1.8–11.4%) and was successfully used to study the uptake of pyrene, benzo[a]pyrene, and benzo[a]anthracene from cigarette smoke. The results indicated that urinary 1-OHP concentration in the smoking group (66.58 ± 70.91 ng/g creatinine) was higher than that observed in the nonsmoking group (58.16 ± 49.48 ng/g creatinine). Urinary 3-OHBaA concentrations in nonsmokers and smokers with 8 mg and 10 mg tar cigarettes were 10.98 ± 4.39 ng/g creatinine, 11.01 ± 13.30 ng/g creatinine, and 9.17 ± 12.89 ng/g creatinine, respectively. Urinary 3-OHBaP concentrations in nonsmokers and smokers with 8 mg and 13 mg tar cigarettes were 1.30 ± 0.20 ng/g creatinine, 2.83 ± 1.78 ng/g creatinine, and 6.00 ± 4.44 ng/g creatinine, respectively. Urinary 1-OHP levels exhibited a significant correlation with BaP yield in cigarette smoke under the Canadian intense smoking condition (y=3.5563x+30.171, R2=0.9916, n=227).